Moho depth and crustal thinning in the Marmara Sea region from gravity data inversion. Issue 2 (3rd February 2017) - Kende, J.; Henry, P.; Bayrakci, G.; Özeren, M. S.; Grall, C.
Abstract: The free‐air gravity in the Marmara Sea reveals that the low density of sedimentary basins is partly compensated in the lower crust. We compiled geophysical upper crust studies to determine the sediment basin geometries in and around the Marmara Sea and corrected the gravity signal from this upper crust geology with the Parker method. Then, assuming long wavelength anomalies in the residual gravity signal is caused by variations in the Moho topography, we inverted the residual to build the Moho topography. The result shows that the Moho is uplifted on an area greater than the Marmara Sea with a maximum crust thinning beneath the basins where the Moho is at about 25 km, 5 km above the reference depth. We then evaluated the Neogene extension by comparing the surface covered by our 3‐D thinned model with the surface covered by an unthinned model with same crustal volume. Comparing this surface with areal extension rate from GPS data, we found a good compatibility indicating that the extension rate averaged over the Sea of Marmara area probably remained close to its present‐day value during major changes of tectonic regime, as the incursion of the North Anatolian Fault system during the Pliocene leads to the establishment of the dominantly strike‐slip present‐day system. We also show that crustal extension is distributed over a wider domain in the lower crust than in the upper crust, and that this may be accounted for by a relatively minor component of lower crustal ductile flow. Key Points: Gravity data corrected from the sedimentary basins are inverted to build a Moho topography The 3‐D crust model obtained is used to compute the total extension in the area, and the result is compared with current extension rate Comparing the basins/Moho geometry, the ductile lower crust flow that could account for the broad thinning south of the NMT is evaluated